Biotic and abiotic determinants of Batrachochytrium dendrobatidis infections in amphibians of the Brazilian Atlantic Forest. (February 2021) - Lambertini, Carolina; Becker, C. Guilherme; M. Belasen, Anat; Valencia-Aguilar, Anyelet; Nunes-de-Almeida, Carlos Henrique L.; Betancourt-Román, Clarisse M.; Rodriguez, David; da Silva Leite, Domingos; Oliveira, Igor S.; Gasparini, João Luiz; Ruggeri, Joice; Mott, Tamí; et al.
Abstract: Latitudinal gradients are linked to the dynamics of infectious diseases. Both prevalence and infection intensity of the amphibian-killing fungus, Batrachochytrium dendrobatidis (Bd), vary with latitude. Here, we tested whether abiotic and biotic factors are associated with Bd infection prevalence and intensity along a large latitudinal gradient across the Brazilian Atlantic Forest. We detected a positive association between infection prevalence and infection intensity with latitude; elevation, temperature and precipitation best explained infection prevalence, while temperature best explained infection intensity. We also detected a positive association between species richness and Bd infections and associations between Bd infections with host reproductive biology and habitat type. This represents the longest and most thoroughly sampled latitudinal gradient of Bd in anuran populations. Our results corroborate earlier findings that abiotic factors are a major determinant of Bd infections and highlight the need for a better understanding of the role that species diversity plays in disease outcomes. Highlights: Batrachochytrium dendrobatidis infections are positively associated with latitude. Environment is a strong determinant of infections in tropical anuran species. The effect of anuran species diversity on pathogen infections is context-dependent.